2021
DOI: 10.3390/insects12121049
|View full text |Cite
|
Sign up to set email alerts
|

Two Complete Mitogenomes of Chalcididae (Hymenoptera: Chalcidoidea): Genome Description and Phylogenetic Implications

Abstract: The complete mitochondrial genomes of two species of Chalcididae were newly sequenced: Brachymeria lasus and Haltichella nipponensis. Both circular mitogenomes are 15,147 and 15,334 bp in total length, respectively, including 13 protein-coding genes (PCGs), two ribosomal RNA genes (rRNAs), and 22 transfer RNA genes (tRNAs) and an A+T-rich region. The nucleotide composition indicated a strong A/T bias. All PCGs of B. lasus and H. nipponensis began with the start codon ATD, except for B. lasus, which had an abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
0
0
Order By: Relevance
“…In summary, with the exception of the BI trees and ML trees constructed from the AA datasets under the homogenous model that did not place Trichogrammatidae closer to the base, the topological trees constructed from our datasets suggested that Chalcididae and Trichogrammatidae may have an earlier origin, a finding consistent with previous studies [ 3 , 43 ]. Comparing the results obtained from our homogeneity and heterogeneity models, we found some inconsistency concerning the classification status of Eupelmidae.…”
Section: Resultssupporting
confidence: 90%
“…In summary, with the exception of the BI trees and ML trees constructed from the AA datasets under the homogenous model that did not place Trichogrammatidae closer to the base, the topological trees constructed from our datasets suggested that Chalcididae and Trichogrammatidae may have an earlier origin, a finding consistent with previous studies [ 3 , 43 ]. Comparing the results obtained from our homogeneity and heterogeneity models, we found some inconsistency concerning the classification status of Eupelmidae.…”
Section: Resultssupporting
confidence: 90%
“…The following sequences were used: Haltichella nipponensis NC060544 (Zhao et al. 2021 ), Metaphycus eriococci NC_056349 (Zhou et al. 2021 ), Aenasius arizonensis NC_045852 (Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…One species from Chalcididae, Haltichella nipponensis (GenBank accession number NC_060544), was used as an outgroup (Zhao et al. 2021 ) ( Table S1 ). To investigate the phylogeny of Exoristobia in Encyrtidae, the family-level relationships within Chalcidoidea were reconstructed by using 13 PCGs with two inference methods (BI and ML).…”
Section: Methodsmentioning
confidence: 99%